Penerapan Communicative Language Teaching (CLT) untuk Meningkatkan Kemampuan Berbicara Siswa Kelas X TKJ di SMKN 5 Palu Tahun Ajaran 2021/2022 - Munifah Munifah (Universitas Tadulako, 2023)
This research aims at investigating the enhancement of students’ speaking ability by applying Communicative Language Teaching (CLT). This research was conducted at SMKN 5 Palu. The subjects were 20 of TKJ A students grade 10. Design of the research used Classroom Action Research conducted in two cycles with three meeting for each using activities; storytelling, role play, game and singing. The research used both qualitative and quantitative data. Data were collected through observation sheet by researcher, field note, questionnaire, and interview. Data were analyzed descriptively and quantitatively. The finding of the research revealed that the applying of CLT can change the students’ learning behavior and attitudes in term of students’ activeness, enthusiasm, participation, and motivation. Moreover, students’ performance on speaking could be enhanced during process of action by achieving the setting up of passing level in cycle 2. Therefore, applying CLT could enhance speaking skill ability.